The Role of Consumer Behavior in Marketing - Ayoker , Lam Bukeje (IJRDO - Journal of Business Management, 2021)
This research paper was carried out to investigate the role of consumer behavior in marketing. Aims of the study are to find the role of consumer behavior in marketing and problems facing the consumer behavior in South Sudan. Researcher used qualitative and quantitative methods for collected data and data was analyzed by statistical package for social science (SPSS). Key findings: the study revealed that the consumer behavior is important in marketing, marketing making customer aware, motivation is the primary drive to purchase decision, cultural factors have strong influence on consumer buyer behavior, marketing plays an important role in economic development, consumer behavior has an important role in improving the standards of living people, respondents agreed that advertisement helps promote new products in the market. In South Sudan there is no consumer behavior protection law. Major recommendations: the researcher has reached to a numbers of important recommendations: government should introduce laws for protection of the consumer’s right, government should increase the income of the workers to improve their living life, the government should stabilize the market prices or reduce taxes rate, and government should provide standard of quality directorate with standard lab for quality. Conclusion: the challenges that are facing consumer behavior in South Sudan includes of factors such as, low supply of goods and services, instability of prices and market fluctuation , low income of the consumer, lack of knowledge to meet the consumers needs and wants, lack of market research, social factors play an essential role in influencing the buying decision of consumers, the most important role of marketers in making a product successful is to meet consumer needs, Information helps in understanding the behavior of the consumers.